Influence of Tear Film Condition in Keratoconus on the Results of Topographic and Tomographic Methods of Corneal Examination. Review - Slonimsky, A. Yu; Averich, V. V.; Mitichkina, T. S. (Oftalmologii͡a, 2025)
Modern methods of corneal visualization (Placido disk keratotopographs, Schimpflug tomographs) play a key role in the diagnosis of various pathological conditions of the cornea, as well as in the planning of surgical interventions. However, despite the accuracy of these devices, there are potential risks of high measurement error associated with destabilization of the precorneal tear film and the presence of signs of dry eye syndrome. Analysis of literature sources revealed a high degree of study of this problem from the position of keratorefractive and cataract surgery. Studies show that tear film instability leads to significant variability of keratometry parameters, increased aberration indices, increased light scattering and appearance of artifacts on topographic maps. In case of dry eye syndrome detection, symptomatic treatment allows to minimize instrument measurement errors and increase functional results of the planned surgical intervention. Of particular interest is the impact of dry eye syndrome on the diagnosis and monitoring of keratoconus, as the two conditions often co-occur. Despite the existence of only a single publication, there are reasons to assume that the combination of signs of dry eye syndrome and SP destabilization in KC may have a significant impact on the results of these diagnostic methods and their interpretation.